Exploring financial sustainability in Islamic secondary schools: importance of good facilities in improving learning process - Mohd. Zain, Nor Razinah; Md. Sidek, Suzana Suhailawaty; Hasbullah, Nurul Fadzlin (NAMA Foundation, 2024)
This research explores financial sustainability of Islamic secondary schools, which is critical to ensure adequate facilities and improving the learning process. This study employs qualitative meta-analysis and documentary research approaches to improve the existing literature on financial sustainability from an Islamic perspective. The existing body of literature suggests that the prevailing discourse of financial sustainability in schools circles around capitalist perspectives. It treats schools as business enterprises, which shifts the true goal of education from educating to profit-making. Financial sustainability is critical to the school management’s capacity to fulfil their responsibilities in providing necessary learning facilities. Good facilities may help the learning process. In relation to Islamic secondary schools, it is found that expensive facilities and equipment are not always necessary, as long as they are provided in acceptable shape for both students and teachers. The presence of such facilities may directly or indirectly enhance the learning process. Ultimately, it improves the quality of education for students. Examples are taken from NAMA Foundation’s sponsorships for selected Islamic secondary schools, which are used to provide good facilities. It demonstrates that financial sustainability is critical for sustaining good facilities, which directly or indirectly improve the learning process.